15 Triggers for the pharmacological management of delirium in palliative care: a mixed methods study. Issue 3 (1st September 2018) - Fairfield, Catherine L; Finucane, Anne M; Spiller, Juliet A
Abstract : Introduction: Delirium is a serious neurocognitive disorder with a high prevalence in palliative care and debate regarding its management is ongoing. Aims: To describe how delirium and its symptoms is documented in patient records To determine the use of delirium screening tools and how these are viewed by staff To identify triggers for pharmacological intervention in delirium management in a terminally ill population. Methods: A retrospective case-note review concerning all patients admitted to a hospice inpatient setting between 1–17th August 2017 and semi-structured interviews with 7 hospice doctors and nurses. Results: 21 patients were reviewed. 62% were screened for delirium using the 4AT on admission. 76% had documented symptoms of delirium and of these 81% died without delirium resolution. There were inconsistencies in the documentation of delirium and the term itself was used infrequently. Non-pharmacological measures were poorly documented. Midazolam was the most commonly used medication. Triggers for pharmacological intervention included failure of non-pharmacological measures distress agitation and risk of patient harm. Nursing staff recognised delirium in its severe form but were less likely to do so in milder cases. Conclusions: Triggers for pharmacological intervention are in-keeping with guidelines however the level of understanding of delirium's presentation varied between participants. This along with the high prevalence of delirium frequent use of midazolam and limited awareness and documentation of non-pharmacological measures (e.g. structured family support) highlights the need for further training and research.